Validation of the Body Concealment Scale for Scleroderma (BCSS): Replication in the Scleroderma Patient-centered Intervention Network (SPIN) Cohort. (March 2017) - ,; Baron, Murray; Bartlett, Susan J.; Furst, Dan; Gottesman, Karen; van den Hoogen, Frank; Mouthon, Luc; Nielson, Warren R.; Poiraudeau, Serge; Riggs, Robert; Sauve, Maureen; Wigley, Fredrick; et al.
Highlights: Psychometrics of the Body Concealment Scale for Scleroderma (BCSS) were evaluated. A bifactor structure fit best, indicating the BCSS be scored as a summed total. Internal consistency reliability and construct validity were strong for the BCSS. The BCSS demonstrated measurement equivalence across sexes and ages. Findings support the BCSS as a patient-reported outcome measure for body concealment. Abstract: Body concealment is an important component of appearance distress for individuals with disfiguring conditions, including scleroderma. The objective was to replicate the validation study of the Body Concealment Scale for Scleroderma (BCSS) among 897 scleroderma patients. The factor structure of the BCSS was evaluated using confirmatory factor analysis and the Multiple-Indicator Multiple-Cause model examined differential item functioning of SWAP items for sex and age. Internal consistency reliability was assessed via Cronbach's alpha. Construct validity was assessed by comparing the BCSS with a measure of body image distress and measures of mental health and pain intensity. Results replicated the original validation study, where a bifactor model provided the best fit. The BCSS demonstrated strong internal consistency reliability and construct validity. Findings further support the BCSS as a valid measure of body concealment in scleroderma and provide new evidence that scores can be compared and combined across sexes and ages.